2018
DOI: 10.2495/wp180091
|View full text |Cite
|
Sign up to set email alerts
|

Path Modelling Analysis of Pollution Sources and Environmental Consequences in River Basins

Abstract: The Portuguese Index of Macroinvertebrates is used as a pollution index in the study of surface water in Portugal. From an environmental perspective, it is necessary to determine the pollution sources affecting surface water. Not only direct discharges of industrial and urban effluents are the cause; possibly the combination of other pollutions sources could result in ecological loss. To comprehend all the cause and effect relationships between pollution sources, water contamination and ecological integrity, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Model 1, Fig. 4, was depicted with only 3 latent variables, "pollution sources", "contamination" and "water quality", similar to one of the models presented in a previous study [17]. In Model 2 "water contamination" was divided into three types of contamination, by "oxygen demands", "nutrients" and "metals".…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Model 1, Fig. 4, was depicted with only 3 latent variables, "pollution sources", "contamination" and "water quality", similar to one of the models presented in a previous study [17]. In Model 2 "water contamination" was divided into three types of contamination, by "oxygen demands", "nutrients" and "metals".…”
Section: Resultsmentioning
confidence: 99%
“…In further studies is intended to use these models to predict IPtI N for Ave River basin, by using new pressure values in sub-basins, in order to verify the validity of these models for future data. As it was demonstrated in another study [17] that the application of SEM-PLS in unpolluted basins can result in lower R-Squared values what would lead to an incorrect classification of IPtI N. Anyhow this methodology should be compared and tested with another river basins, but it is warned that not the same variables can be always used because the dismissed variables through multicollinearity might not be the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such results prove that sustainable agriculture can not harm, but even, improve water quality when combined with forested land uses, as barriers of contamination from runoff or soil erosion. In studies of similar scope, it was used PLS-PM (Partial Leas Squares Path -Modelling) to establish cause-effect interactions between pressures with ecological status [50][51][52], in Ave River Basin. The authors concluded that livestock and effluent discharges were major threats to water quality, but in such analysis, the only studied landscape metric was only the area percentage for different land-use types "pz".…”
Section: Resultsmentioning
confidence: 99%
“…For the assessment of the risk of groundwater contamination, it is crucial to conduct a survey about the connection between several factors that may increase the radon diffusion from rocks to the water such as, the weathering rate of U-bearing minerals under certain specific pH conditions [8]- [13], rock hydraulic diffusivity [14]- [16], and the emanation coefficient [17]. Several environmental studies used the structural equation modelling-partial least squares (SEM-PLS) models to establish common approaches in large flood management [18], ecological surveys [19], [20], and radiological impact in groundwater [2]. The application of cluster analysis with complex structural models was previously performed by Martins et al [2] to study the effect of some factors on radon contamination in the aquifer system.…”
Section: Introductionmentioning
confidence: 99%